Desenvolvimento de uma nova metodologia MISPE para extração de taninos - Martins, Rafael Oliveira (2019)
The present work deals with the development of a new SPE extraction methodology to concentrate bioactive compounds known as condensed tannins in complex matrices, besides removing the possible interferents present in these matrices. Aiming at reducing sample preparation time and achieving a more selective analysis for these compounds.